2022
DOI: 10.3390/toxins14080515
|View full text |Cite
|
Sign up to set email alerts
|

Production of Satratoxin G and H Is Tightly Linked to Sporulation in Stachybotrys chartarum

Abstract: Stachybotrys chartarum is a toxigenic fungus that is frequently isolated from damp building materials or improperly stored forage. Macrocyclic trichothecenes and in particular satratoxins are the most potent mycotoxins known to be produced by this fungus. Exposure of humans or animals to these secondary metabolites can be associated with severe health problems. To assess the pathogenic potential of S. chartarum isolates, it is essential to cultivate them under conditions that reliably promote toxin production.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…Mycotoxins of several fungi are known to be associated with sporulation and are secreted by growing colonies ( 61 ), and a link between secondary metabolism and sporulation is a common feature in many filamentous fungi ( 62 ). Previously, similar results were obtained with S. chartarum ( 57 ), and, therefore, our observations are in good agreement with published data.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Mycotoxins of several fungi are known to be associated with sporulation and are secreted by growing colonies ( 61 ), and a link between secondary metabolism and sporulation is a common feature in many filamentous fungi ( 62 ). Previously, similar results were obtained with S. chartarum ( 57 ), and, therefore, our observations are in good agreement with published data.…”
Section: Discussionsupporting
confidence: 94%
“…We included three S. chartarum strains in this study that are known for their effective production of macrocyclic trichothecenes (MTs) and stachybotrylactam (STLAC) ( 6 , 9 , 38 , 54 ). Since our previously published data demonstrated that satratoxin production is tightly linked to sporulation ( 57 ), this work considered the size of the resulting colonies and their level of sporulation. The selected strains come from three substrates, namely, oats (ATCC 34916), building material from an apartment in Oakland (IBT 40293), and oregano (DSM 114129).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A thorough search using the AntiFungi algorithm revealed the noteworthy secondary metabolite napthopyrone, a fungal predator-protecting secondary metabolite [ 70 ] ( Table 7 ). Moreover, comparative genomics results revealed the presence of toxin-related genes, comprising those related to killer toxin α/β, satratoxin, and aflatoxins identified in fungal genera such as Kluyveromyces , Stachybotrys , Aspergillus , the teleomorph genus Neosartorya , and the KP4 killer toxin from Ustilago maydis P4 virus [ 10 , 71 , 72 ] ( Table 8 ).…”
Section: Resultsmentioning
confidence: 99%